Novel inorganic fillers of 1D hydroxyapatite nanowires induced superior energy storage performances of P(VDF–HFP)-based composite films. Issue 40 (28th September 2022) - Cheng, Yu; Pan, Zhongbin; Chen, Hanxi; Ding, Xiangping; Li, Zhicheng; Fan, Xu; Liu, Jinjun; Li, Peng; Yu, Jinhong; Zhai, Jiwei
Abstract : Newly one-dimensional hydroxyapatite nanowires are synthesized and applied in P(VDF–HFP) nanocomposites for energy storage application. Excellent U d of ∼27.6 J cm −3 accompanied with high η of ∼72.9% at E b of 650 MV m −1 are achieved. Abstract : High-performance flexible dielectric capacitors have a decisive effect in advanced electronics and electrical power systems. Nevertheless, the discharge energy density ( U d ) of dielectric capacitors is bounded by their weak breakdown strength ( E b ) and low dielectric constant ( K ). In this work, mediate dielectric constant one-dimensional hydroxyapatite nanowires (HAP NWs) were synthesized and applied in poly(vinylidene fluoride- co -hexafluoropropene)-based (P(VDF–HFP)) nanocomposites for energy storage application. To mitigate electric field distortion and suppress free charge migration in nanocomposites, Al2 O3 was insulated as an interfacial layer incorporated between 1D HAP NWs and polymer matrices, which were identified via phase field simulations and experimental results. Accordingly, P(VDF–HFP)/HAP@Al2 O3 NWs composite films exhibit an excellent U d of ∼27.6 J cm −3 accompanied by a high charging/discharging efficiency ( η ) of ∼72.9% at 650 MV m −1, which is ∼190% over neat P(VDF–HFP) (∼9.5 J cm −3 at 500 MV m −1 ) and ∼2200% improvements of bench-mark biaxially oriented polypropylene (∼1.2 J cm −3 at 650 MV m −1 ). This research offers a paradigmatic design to polymer-based composite films with high U d and η for application in dielectric capacitors.